The Role of Antithrombotic Therapy in Heart Failure - Chrysohoou, Christina; Magkas, Nikolaos; Antoniou, Christos-Konstantinos; Manolakou, Panagiota; Laina, Aggeliki; Tousoulis, Dimitrios (Current Pharmaceutical Design, 2020)
Heart failure is a major contributor to global morbidity and mortality burden affecting approximately 1-2% of adults in developed countries, mounting to over 10% in individuals aged >70 years old. Heart failure is characterized by a prothrombotic state and increased rates of stroke and thromboembolism have been reported in heart failure patients compared with the general population. However, the impact of antithrombotic therapy on heart failure remains controversial. Administration of antiplatelet or anticoagulant therapy is the obvious (and well-established) choice in heart failure patients with cardiovascular comorbidity that necessitates their use, such as coronary artery disease or atrial fibrillation. In contrast, antithrombotic therapy has not demonstrated any clear benefit when administered for heart failure per se, i.e. with heart failure being the sole indication. Randomized studies have reported decreased stroke rates with warfarin use in patients with heart failure with reduced left ventricular ejection fraction, but at the expense of excessive bleeding. Non-vitamin K oral anticoagulants have shown a better safety profile in heart failure patients with atrial fibrillation compared with warfarin, however, current evidence about their role in heart failure with sinus rhythm is inconclusive and further research is needed. In the present review, we discuss the role of antithrombotic therapy in heart failure (beyond coronary artery disease), aiming to summarize evidence regarding the thrombotic risk and the role of antiplatelet and anticoagulant agents in patients with heart failure.
Keywords: vitamin K antagonists